Localization of preschoolers' behavior on four playgrounds. - Rallis, Mary. (University of Ottawa (Canada), 1993)
Naturalistic observations were made on 72 preschoolers in four daycare centres to determine whether preschoolers preferred certain areas of the playground and whether specific social and cognitive behaviors were localized in particular parts of the playground. Each playground area was classified in one of four ways (enclosed/private areas, play structures, pavement, and sand) to determine whether different areas elicit different behaviors. Whether individual differences in internalizing or externalizing behaviors or sex influenced amount of time spent in different types of areas or number of areas played in were also examined. Results indicated that preschoolers spent more time on pavement and sand than on play structures and private areas and that there was more unoccupied activity in the former two areas than in the latter. Sand appeared to promote fine motor play whereas play structures promoted gross motor play. Results did not support the hypothesis that externalizing or internalizing behaviors or sex influenced the use of space.
Keywords: Psychology, Clinical.